Cryogenics free production of hyperpolarized 129Xe and 83Kr for biomedical MRI applications - Hughes-Riley, Theodore; Six, Joseph S.; Lilburn, D.M.L.; Stupic, Karl F.; Dorkes, Alan C.; Shaw, Dominick E.; Pavlovskaya, Galina E.; Meersmann, Thomas (Elsevier, 2013)
As an alternative to cryogenic gas handling, hyperpolarized (hp) gas mixtures were extracted directly from the spin exchange optical pumping (SEOP) process through expansion followed by compression to ambient pressure for biomedical MRI applications. The omission of cryogenic gas separation generally requires the usage of high xenon or krypton concentrations at low SEOP gas pressures to generate hp 129Xe or hp 83Kr with sufficient MR signal intensity for imaging applications. Two different extraction schemes for the hp gasses were explored with focus on the preservation of the nuclear spin polarization. It was found that an extraction scheme based on an inflatable, pressure controlled balloon is sufficient for hp 129Xe handling, while 83Kr can efficiently be extracted through a single cycle piston pump. The extraction methods were tested for ex vivo MRI applications with excised rat lungs. Precise mixing of the hp gases with oxygen, which may be of interest for potential in vivo applications, was accomplished during the extraction process using a piston pump. The 83Kr bulk gas phase T1 relaxation in the mixtures containing more than approximately 1% O2 was found to be slower than that of 129Xe in corresponding mixtures. The experimental setup also facilitated 129Xe T1 relaxation measurements as a function of O2 concentration within excised lungs.